2006
DOI: 10.1300/j027v25n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Depression Care for the Elderly: Reducing Barriers to Evidence-Based Practice

Abstract: This paper provides an overview of five key bodies of evidence identifying: (1) Characteristics of depression among older adults -- its prevalence, risk factors and illness course, and impact on functional status, mortality, use of health services, and health care costs; (2) Effective Interventions, including pharmacologic, psychotherapies, care management, and combined intervention models; (3) Known Barriers to depression care including patient, provider and service system barriers; (4) Effective Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 238 publications
1
49
0
1
Order By: Relevance
“…[2][3][4] In addition to ethnic minority status, individual-level barriers to MH service use among older adults include lack of insight into psychological problems, high levels of perceived stigma about MH problems, and beliefs that they can handle these problems alone. [5][6][7][8][9] Contributors to treatment use and/or perceived treatment need include diagnosed mental disorders, mood, and anxiety symptom severity, serious psychological distress, suicidal behaviors, chronic illnesses, chronic pain, and higher education. 3,5,9,10 Epidemiologic studies show that adults of all ages with substance use disorders (SUD) or comorbid SUD and depression or other mental disorders are more likely than those without SUD or a co-occurring mental disorder to use MH services and/or perceive unmet treatment need.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In addition to ethnic minority status, individual-level barriers to MH service use among older adults include lack of insight into psychological problems, high levels of perceived stigma about MH problems, and beliefs that they can handle these problems alone. [5][6][7][8][9] Contributors to treatment use and/or perceived treatment need include diagnosed mental disorders, mood, and anxiety symptom severity, serious psychological distress, suicidal behaviors, chronic illnesses, chronic pain, and higher education. 3,5,9,10 Epidemiologic studies show that adults of all ages with substance use disorders (SUD) or comorbid SUD and depression or other mental disorders are more likely than those without SUD or a co-occurring mental disorder to use MH services and/or perceive unmet treatment need.…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to their underrepresentation in depression care are system (lack of access to treatment and trained health providers) and person (stigma, lack of knowledge about symptoms, lack of trust of providers) level factors (Conner et al, 2010; Ell, 2006; Gum et al, 2009). Studies also show that older African Americans may prefer nondrug approaches and have poorer compliance to drug therapies than their white counterparts (Kales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that as low as one-tenth of depressed older adults received treatment for their depressed emotion [15]. The common barrier is that some symptoms such as changes in sleep, appetite, fatigue and loss of interests in usual activities can be overlooked as a part of aging.…”
Section: Introductionmentioning
confidence: 99%